Take it and leave it: Banks' balance sheet optimization and targeted longer-term refinancing operations - Michael Sigmund; Johannes Wächtler; Philip Schuster; Robert Ferstl; María Teresa Valderrama (Oesterreichische Nationalbank (OeNB), 2024)
We develop and solve a dynamic optimization model of a bank's balance sheet, highlighting the critical factors influencing banks' optimization dynamics: balance sheet adjustment costs and the spreads between bank-specific lending and deposit rates and the interbank rate. We apply the model to evaluate the impact of the European Central Bank's (ECB) targeted longer-term refinancing operations (TLTROs) on banks in a simulation exercise, and we estimate the policy functions with monthly data from 200 large euro area banks spanning from 2007 to 2021. The estimation results confirm the theoretical prediction and simulations that the TLTRO programs did not stimulate lending to the private sector, but banks mainly increased their central bank assets and liabilities, especially with TLTRO III in 2020, in which the ECB implemented a reversal of its policy rates by setting the TLTRO rate below the deposit facility rate.
Keywords: E43; E44; E58; F42; G20; 330; Monetary policy transmission; dynamic programming; unconventional monetary policy; panel vector autoregression